Association of type and location of BRCA1 and BRCA2 mutations with risk of breast and ovarian cancer - Rebbeck, Timothy; Hamann, Ute; Sutter, Christian; Bartram, Claus R.; Dikow, Nicola (The journal of the American Medical Association, 2015)
Importance Limited information about the relationship between specific mutations inBRCA1orBRCA2(BRCA1/2) and cancer risk exists. Objective To identify mutation-specific cancer risks for carriers ofBRCA1/2. Design, Setting, and Participants Observational study of women who were ascertained between 1937 and 2011 (median, 1999) and found to carry disease-associatedBRCA1orBRCA2mutations. The international sample comprised 19 581 carriers ofBRCA1mutations and 11 900 carriers ofBRCA2mutations from 55 centers in 33 countries on 6 continents. We estimated hazard ratios for breast and ovarian cancer based on mutation type, function, and nucleotide position. We also estimated RHR, the ratio of breast vs ovarian cancer hazard ratios. A value of RHR greater than 1 indicated elevated breast cancer risk; a value of RHR less than 1 indicated elevated ovarian cancer risk. Exposures Mutations ofBRCA1orBRCA2. Main Outcomes and Measures Breast and ovarian cancer risks. Results AmongBRCA1mutation carriers, 9052 women (46%) were diagnosed with breast cancer, 2317 (12%) with ovarian cancer, 1041 (5%) with breast and ovarian cancer, and 7171 (37%) without cancer. AmongBRCA2mutation carriers, 6180 women (52%) were diagnosed with breast cancer, 682 (6%) with ovarian cancer, 272 (2%) with breast and ovarian cancer, and 4766 (40%) without cancer. InBRCA1, we identified 3 breast cancer cluster regions (BCCRs) located at c.179 to c.505 (BCCR1; RHR = 1.46; 95% CI, 1.22-1.74;P = 2 × 10−6), c.4328 to c.4945 (BCCR2; RHR = 1.34; 95% CI, 1.01-1.78;P = .04), and c. 5261 to c.5563 (BCCR2′, RHR = 1.38; 95% CI, 1.22-1.55;P = 6 × 10−9). We also identified an ovarian cancer cluster region (OCCR) from c.1380 to c.4062 (approximately exon 11) with RHR = 0.62 (95% CI, 0.56-0.70;P = 9 × 10−17). InBRCA2, we observed multiple BCCRs spanning c.1 to c.596 (BCCR1; RHR = 1.71; 95% CI, 1.06-2.78;P = .03), c.772 to c.1806 (BCCR1′; RHR = 1.63; 95% CI, 1.10-2.40;P = .01), and c.7394 to c.8904 (BCCR2; RHR = 2.31; 95% CI, 1.69-3.16;P = .00002). We also identified 3 OCCRs: the first (OCCR1) spanned c.3249 to c.5681 that was adjacent to c.5946delT (6174delT; RHR = 0.51; 95% CI, 0.44-0.60;P = 6 × 10−17). The second OCCR spanned c.6645 to c.7471 (OCCR2; RHR = 0.57; 95% CI, 0.41-0.80;P = .001). Mutations conferring nonsense-mediated decay were associated with differential breast or ovarian cancer risks and an earlier age of breast cancer diagnosis for bothBRCA1andBRCA2mutation carriers. Conclusions and Relevance Breast and ovarian cancer risks varied by type and location ofBRCA1/2mutations. With appropriate validation, these data may have implications for risk assessment and cancer prevention decision making for carriers ofBRCA1andBRCA2mutations.
Gesehen am 17.06.2020